Analisis Kepatuhan Bendahara Pemerintah Dalam Aspek Perpajakan Pada Dinas Kesehatan Kabupaten Siak - Assidiki, Shandy Luthfi; Aristi, Mentari Dwi; Agustiawan (Asosiasi Dosen Akuntansi Indonesia, 2024)
The purpose of this study was to analyze the compliance of government treasurers in taxation aspects and to identify factors that influence the compliance of Siak Regency government treasurers in taxation aspects. The object of this study was the Siak Regency Health Office. The research informants were determined by the snowball sampling method consisting of the Head of the Health Office, the Treasurer of the Siak Regency Health Office and the Administration Staff. The results of the study stated that the Regional Treasurer already understood how to carry out taxation procedures following the regulations for implementing the self-assessment system. Factors that influence the compliance of the Regional Treasurer in taxation aspects are the lack of coordination with the Financial Operations Agency (BOK) at the Health Office, the difference in the Monthly Tax Returns which affects the Annual Tax Returns, as a result, the Health Office is late in submitting Tax Returns compared to other offices